Upaya Peningkatan Belajar Tematik Melalui Model Pembelajaran Kooperatif Tipe Make A Match - Karmilah Karmilah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to improve learning outcomes of thematic learning themes 3 sub-themes of my daily tasks at home in class II B SD Negeri 47 Lubuklinggau in the 2021/2022 academic year by applying the make a match type of cooperative learning model. The method used in this classroom action research is the Kurt Lewin model in which there are 4 (four) stages, namely planning, action, observation, and reflection. The subjects in this study were second grade students of SD Negeri 47 Lubuklinggau which consisted of 25 students. The results showed that the application of the make a match type cooperative model could increase student activity. On the results of the observation of student activities in the first cycle, namely 70.83, and increased to 91.7 in the second cycle. The increase in student learning outcomes can be seen from the average score of Indonesian language subjects in the pre-cycle of 62.00 with a percentage of 48%, in the first cycle it became 71.20, with a percentage of 68%, and increased to 83.20, with a percentage 88% in cycle II. In mathematics, there was also an increase in the pre-cycle by 61.60, with a percentage of 40%, in the first cycle to 73.20 with a percentage of 72%, and increased to 84.40, with a percentage of 84% in the second cycle. In conclusion, the cooperative learning model of the make a match type can improve thematic learning outcomes. Keywords: Learning Outcomes, Thematic, Make a Match Cooperative Model